Das possibilidades do impossível : leituras do outro vivente em Jaula, de Astrid Cabral - Silva, Jamerson Eduardo Reis (2018)
In order to discuss the relation between literature and animality present in the anthology Jaula (2006) by Astrid Cabral, a Brazilian poet born in Amazonas, this study offers readings of the ambiguous and undeniable presence of the other living beings in the work. From three initially distinct points that ultimately complement each other, we try to reach a poetic act, which according to what we think, tries to deal with the possibilities of the impossible present within the cited relation. Formulated mainly from the perspective of the men and humanity, in favor of these, the categories which rule our relations with animals, not only created a void by constantly removing any possibility of those others named “irrational” but also used this void to exercise an absolute power upon them. Trying not to revert the prejudice of this Cartesian and anthropocentric logic but rather deal with it, in the sense of comprehend its extension and face it, Astrid’s Jaula renders the space of the literature to the other living beings revealing by doing so our ignorance for “what all birds must know”. In an attempt to interpret this movement of the work which may seem simple at first but reveals to be arguably multiple in its realization, we do too multiply by three our efforts. In the first moment, we seek to discuss the construction of the borders between the categories: humanity and animality and how the anthology articulates itself to restore the undeniable ambiguity present in these. Moving forward, we dedicate ourselves to the question of representation and non-representation of the animals in literature in order to comprehend how they turn into an interface, in which the human view finds itself more close to the animality. Lastly, we turn ourselves to the taxonomic-literary aspects of Astrid’s Jaula that it has inherited from the tradition of the medieval and zoopoetic bestiaries of the XX century. The author rearrange this tradition using the possibilities within the genre to compose, poetically, not only a space to her other living beings made of letters but also a trap that capture and disavows the Adamic order of the world. Keywords: Animality; Brazilian Literature; Astrid Cabral.